Prenatal diagnosis, hospital characteristics, and mortality in transposition of the great arteries. Issue 9 (14th June 2016) - Lara, Diego A.; Fixler, David E.; Ethen, Mary K.; Canfield, Mark A.; Nembhard, Wendy N.; Morris, Shaine A.
Abstract : Background: The role of prenatal diagnosis in reducing neonatal mortality from transposition of the great arteries (TGA) is controversial. Factors affected by prenatal diagnosis such as proximity at birth to a cardiac surgical center (CSC) and CSC volume are associated with mortality in congenital heart disease. The purpose of the study was to determine the associations between prenatal diagnosis, distance from birthplace to a CSC, CSC TGA volume, and neonatal mortality in patients with TGA. Methods: The Texas Birth Defects Registry was queried for all live born infants with TGA from 1999 to 2007. Four hundred sixty‐eight cases of TGA were included. Results: Forty‐eight patients (10.3%) were prenatally diagnosed, and 20 patients died before age 28 days (4.3%). Neither prenatal diagnosis nor close proximity to a CSC at birth ( p > 0.05) were associated with decreased mortality. Low CSC TGA volume was associated with increased mortality ( p < 0.0002). Mortality at the CSCs with <5 patients per year was 9.6%; CSCs with 5 to 10 patients per year had 0% mortality, and those with >10 patients per year had 2.3% mortality. In multivariable logistic regression, only preterm birth (odds ratio, 7.05; 95% confidence interval, 4.13–12.05) and lower CSC volume ( p < 0.001) were associated with neonatal mortality, although prenatal diagnosis attenuated the detrimental association of lower volume CSCs with higher mortality ( p for interaction = 0.047). Conclusion: Lower CSC TGA patient volume was associated with higher neonatal mortality. Prenatal diagnosis may improve survival in lower volume CSCs. Birth Defects Research (Part A) 106:739–748, 2016. © 2016 Wiley Periodicals, Inc.